Effect of authentic leadership on Nurses' psychological distress and turnover intention - Ali D. Abousoliman; Hagar Mahmoud Hamed (Elsevier, 2024)
Background: At healthcare institutions, authentic leadership style has a crucial role in creating a positive work environment where nurses show higher levels of engagement and less intent to leave their jobs in environments where authentic leadership has been exhibited. Aim: This study sought to investigate authentic leadership effects on nurses' psychological distress and their turnover intention. Design: A cross-sectional descriptive study. Settings: The study was conducted at Kafr Elsheikh University hospitals in Egypt. Participants: Nurses working at Kafr Elsheikh University hospitals in Egypt were enrolled (N = 285). Methods: Authentic leadership self-assessment questionnaire, Kessler psychological distress scale, and Michaels and Spector's (1982) 3-item scale to measure turnover intentions were used. Results: Authentic leadership style has a statistically significant negative relationship with psychological distress (r = -0.28), and turnover intention was found (r = -0.18) retrospectively. Whereas the results indicated that there is a statistically significant positive relationship between psychological distress and turnover intention (r = 0.52). Conclusion: This study provided additional knowledge about authentic leadership behaviors' role in promoting psychological well-being, decreased level of nurses' psychological distress, and their intention to leave their work.